2013
DOI: 10.1080/02640414.2013.830189
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in physical fitness among elementary school children

Abstract: There is empirical evidence that children's physical activity is dependent on climatic conditions. In addition, a correlation between physical activity level and physical fitness has been identified. In this longitudinal study, we investigate whether seasons have an influence on physical fitness. A total of 145 German elementary school children were tested every six months over a two-year period. We used the German Motor Test 6-18 to assess physical fitness. Performance in the 6-min endurance run (P < 0.001), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 33 publications
6
13
0
Order By: Relevance
“…In comparison, central European studies showed that 13-33 % of primary school children are overweight and obese [11,14,15,19,20]. In accordance to other studies [10,11,16], overweight and obese children showed significantly lower motor performance in the majority of test items. This might be due to the fact that the excess body fat of overweight and obese children is an extra load to be moved during weight-bearing tasks [21].…”
Section: Statisticssupporting
confidence: 87%
See 4 more Smart Citations
“…In comparison, central European studies showed that 13-33 % of primary school children are overweight and obese [11,14,15,19,20]. In accordance to other studies [10,11,16], overweight and obese children showed significantly lower motor performance in the majority of test items. This might be due to the fact that the excess body fat of overweight and obese children is an extra load to be moved during weight-bearing tasks [21].…”
Section: Statisticssupporting
confidence: 87%
“…Well in accordance, Augste and Künzell [11] found in a longitudinal study over 2 years among 83 German primary school children that the BMI was the most important predictor for motor performance.…”
Section: Statisticssupporting
confidence: 50%
See 3 more Smart Citations